GENOTYPES OF MYCOBACTERIUM TUBERCULOSIS ISOLATES FROM DIFFERENT ORGANS OF PATIENTS WITH GENERALIZED TB AND HIV-COINFECTION - A. A. Gerasimova; A. A. Vyazovaya; M. Yu. Mayskaya; I. V. Mokrousov; O. V. Narvskaya (Инфекция и иммунитет, 2018)
.